KONSEP WARIS ŻAWIL ARHAM MENURUT MAZHAB SYAFI’I DAN HAMBALI - Fadheli, Mohammad Farid; Umami, Hafidhul (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2023)
The issue of inheritance in Islam is presented most comprehensively by the Quran and can be considered thoroughly addressed. Inheritance poses a sensitive and challenging problem in court institutions. The study of inheritance law is undertaken to preserve family harmony, as it involves the distribution of property among the heirs left behind. Heirs can be categorized into three groups:1. żawil furudl. 2. ‘ashabah. 3. żawilarḥam. Scholars agree that żawil furudl and żawil ‘ashabah are the heirs of the deceased. Regarding the inheritance rights of żawilarḥam (heirs who do not have a specific share or inheritance right, both in the Quran and Sunnah, i.e., those who have a blood relationship with the deceased only through the female side), scholars do not unanimously agree. According to the majority of the Shafi'i school, żawil arḥam is not entitled to inherit, and the rightful recipient is the baitul mal, due to the absence of clear guidance regarding żawil arham. On the other hand, according to contemporary scholars of the Shafi'i school, if the baitul mal is not organized, then the inheritance is given to the heirs of żawil arham. Meanwhile, according to the Hanbali school, żawil arham is entitled to inherit because they are heirs with a blood relationship to the deceased.